Interfaith marriage in Islam: a feminist approach toward the Qu’ranic ethics of Islamic marriage - Tahiri, Halima (iQual. Revista de Género e Igualdad, 2024)
According to Islamic law regardless of the school of thought, intermarriage is prohibited, except in the case of a Muslim man marrying a scriptural woman (Kitabiya). A Muslim woman may not marry a non-Muslim man, while a Muslim man may marry a non-Muslim woman (people of the book, including Christianity and Judaism). For Muslim scholars, there is a room for exception in which Muslim women may marry non-Muslim men, and this exception can occur only under one condition: the convergence of non-Muslim men into Islam. However, Feminist scholars and thinkers such as Asma Barlas 2002, Asma Lamrabat 2016, and Amina Wadud 1999 argued that these rules seem more restrictive to both Muslim women and non-Muslim men who wish to marry, and that the arguments used by Muslim thinkers and often adopted and followed by ordinary Muslims to justify the continued acceptance of these rules are incompatible with women’s rights and freedom. For them, Muslim women should have a marital choice similar to their Muslim male counterparts. The goal of this research paper is to critically discuss the sources from which this rule is derived, and the process through which it is interpreted by feminist thinkers and Muslim scholars.